Pengaruh Non Performing Loan Dan Biaya Oprasional Pendapatan Operasional Terhadap Laba Bersih - Wida, Oda; Zakaria Hakim, Heikal Muhammad; Huda, Syamsul (AKTSAR: Jurnal Akuntansi Syariah, 2019)
The purpose of this study was to analyze the effect of operational income opportunity (BOPO), Non-Performing Loans (NPL) on net income of 10 conventional banks that have the highest assets according to the financial services authority (OJK) in 2017. The results showed that non-performing loan does not have a significant effect on net income, bopo has an effect on net income. Based on the results of determination coefficient analysis, the independent variables can explain the effect on net profit of 55.5%, while the remainder is explained by other variables not explained in this study. Based on the results of the f test, the independent variables simultaneously have a significant effect on net profit.